Validasi Approaches to Learning and Studying Inventory di Fakultas Kedokteran Universitas Gadjah Mada Yogyakarta - Michael A. Leman; Rossi Sanusi; Yayi Suryo Prabandari (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2014)
Background: Short version instruments are being developed to meet the needs of social sciences researchers who simulataneously use a number of instruments. The Approaches to Learning and Studying Inventory (ALSI) is a short version instrument to measure learning approaches used by students. This analysis is part of a study that is published in different medical education periodicals. The objective of this assessment was to validate the ALSI in a population of second year medical students of the Gadjah Mada University Faculty of Medicine (GMU FM), Yogyakarta.Method: 225 second year students in the regular program at the GMU FM were invited to complete the ALSI questionnaire. To suport construct validities of ALSI, an item’ validity, Crönbach alpha, factor analysis, convergent validity, and discriminant validity were measured.Results: A total of 160 students participated in this study (71,11% response rate). The data collected did not support the construct validities of ALSI.Conclusion: ALSI requires improvement, in particular the items of the surface approach subscale. Instead of the initial five subscales, it is probably more appropriate if the instrument is divided in only three subscales - surface approach, effort management-organized studying, and deep approach-monitoring studying.